2009
DOI: 10.1086/bblv217n1p50
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation of Crayfish Hindgut

Abstract: The crayfish hindgut is a morphologically differentiated tube that varies along its length in the distribution of muscles and glands, contractile properties, serotonergic innervation, patterns of 5-HT receptor expression, and sensitivity to serotonin (5-HT). Anatomical differences divide the hindgut into five distinct segments along its length. Spontaneous pulsatile contractions produced by the isolated hindgut decrease in force and increase in frequency along the anterior-posterior axis. Central input to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The long hindgut is divided into five distinct segments according to anatomical differences (Musolf et al, 2009) as shown in Fig. S4 and Pl-TEP expression pattern in different parts of crayfish digestive organs was then determined.…”
Section: Tissue Distribution Of Pl-a2m1 Pl-a2m2 and Pl-tep Mrnamentioning
confidence: 99%
“…The long hindgut is divided into five distinct segments according to anatomical differences (Musolf et al, 2009) as shown in Fig. S4 and Pl-TEP expression pattern in different parts of crayfish digestive organs was then determined.…”
Section: Tissue Distribution Of Pl-a2m1 Pl-a2m2 and Pl-tep Mrnamentioning
confidence: 99%
“…The most recent comprehensive overview of the crayfish hindgut was complied in a dissertation by Dr. Barbara E. Musolf (2007, Georgia State University, Atlanta, Georgia, USA), who focused primarily on serotonergic modulation and innervation (Musolf et al, 2009). Crustacean hindguts were first studied over 100 years ago by Alexandrowicz, a pioneer in comparative anatomy (Alexandrowicz, 1909), who described the various aspects of their innervation.…”
Section: Introductionmentioning
confidence: 99%